The Impact of Software Piracy on Inclusive Human Development: Evidence from Africa - Simplice A. Asongu; Antonio Rodríguez Andrés (African Governance and Development Institute (AGDI), 2014)
This paper examines two dimensions of the software piracy-development nexus to complement existing formal literature. It empirically assesses the incidence of piracy on the Human Development Index (HDI) and its constituents and then the instrumentality of Intellectual Property Right (IPR) treaties (laws) in the linkages. An instrumental variable or Two-stage least squares is applied on panel of 11 African countries with data for the period 2000-2010. Three main findings are established: (1) software piracy has a negative incidence on inequality adjusted human development; (2) the unappealing effect of piracy on the HDI is fuelled by per capita economic prosperity and life expectancy components of human emancipation; (3) software piracy increases literacy. Two major policy implications have been retained from the findings. Firstly, adherence to international IPRs protection treaties (laws) may not impede per capita economic prosperity and could improve life-expectancy. Secondly, adoption of tight IPRs regimes may negatively affect human development by diminishing the literacy rate and restricting diffusion of knowledge.
Keywords: K42; O34; O38; O47; O57; 330; Software piracy; Human development; Intellectual property rights; Panel data; Instrumental variables